EXAMINING THE ROLE OF REFLECTIVE PRACTICES IN ENHANCING CLINICAL REASONING SKILLS AMONG NURSING STUDENTS IN THE COLLEGE OF NURSING NMU MULTAN - MANZOOR , R; MAJEED, S; KHALID , R; ANWAR , M (Biological and Clinical Sciences Research Journal, 2024)
Clinical reasoning is a vital skill for nursing students, enabling them to provide high-quality patient care. Reflective practices, such as journaling and structured feedback, have been recognized as effective tools for enhancing clinical reasoning skills. However, limited research exists on the integration of reflective practices in nursing education in Pakistan. Objective: To examine the role of reflective practices in enhancing clinical reasoning skills among nursing students at the College of Nursing, Nishtar Medical University, Multan. Methods: A descriptive cross-sectional study was conducted with 130 BSN nursing students. Data were collected using a validated questionnaire assessing the use of reflective practices, clinical reasoning skills, and associated challenges and facilitators. Descriptive statistics were employed to analyze the data using IBM SPSS version 26. Results: The majority of students (90%) reported that reflective practices improved their clinical reasoning skills. Key challenges included lack of time (65.4%) and inadequate guidance from educators (34.6%). Facilitators included educator support (69.2%) and structured reflective tools (65.4%). Conclusion: Reflective practices significantly enhance clinical reasoning skills among nursing students in Pakistan. Addressing barriers such as workload and training gaps can optimize the use of reflective practices, leading to improved nursing education and patient outcomes.